Data-Driven Cataloguing of AICCRA Innovations and Spillover Effects - Ewell, Hanna; Tobon, Hector; Giombini, Valentina; Chaves, Laura; Girvetz, Evan (2025)
This Info Note presents the development of AICCRA’s data-driven Innovation Catalogue, a digital platform designed to make climate-smart agriculture (CSA) and climate information services (CIS) innovations visible, comparable, and actionable across six African countries. The document describes how standardized data governance, interoperability with MARLO and CLARISA, and a user-centered design process enable the catalogue to track scaling readiness, demand, institutional uptake, inclusion outcomes, and regional spillover potential. It highlights how the catalogue supports responsible and adaptive scaling decisions by integrating evidence on technical performance, investment and demand signals, and sustained use within systems. The Innovation Catalogue functions as a living, strategic portfolio that connects innovations with partners, guides cross-country learning, and lays the foundation for long-term impact beyond AICCRA.